Penerapan Upah Minimum dan Jaminan Sosial Bagi Pekerja di Kota Kupang - Yuliana Ketrin Nalo; Norani Asnawi; Vergilius Septyanto Lamabelawa (Student Research Journal, 2026)
This study aims to examine the implementation of minimum wages and social security for workers in Kupang City, as well as the factors influencing their implementation. This study is important given that minimum wages and social security are fundamental rights of workers that must be fulfilled to ensure the well-being and protection of the workforce. The research method used in this study is a legal-empirical approach utilizing primary and secondary data obtained through interviews, literature reviews, legislation, expert legal opinions, as well as books and journals related to the research. This approach was used to obtain an overview of the actual conditions regarding the implementation of workers’ rights in Kupang City. The research results indicate that the implementation of the minimum wage and social security for workers in Kupang City has not been fully realized. The implementation of the minimum wage is influenced by labor productivity, inflation rates, economic conditions, social conditions, and government policies. Meanwhile, the implementation of employment social security still faces obstacles in the form of low legal awareness among workers and employers, limited government oversight, and suboptimal compliance by companies in fulfilling workers’ rights.